2013
DOI: 10.3892/mmr.2013.1640
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone induces apoptosis in RKO cells through the generation of reactive oxygen species and the mitochondrial pathway

Abstract: Abstract. Alantolactone, a methanol extract of Inula helenium, possesses anticancer properties in a number of cancer cell lines. However, its anticancer effect on human colorectal cancer cells and the underlying mechanisms remain to be elucidated. In the present study, the effects of alantolactone on cell viability and apoptosis in RKO human colon cancer cells were investigated. Alantolactone treatment of RKO cells was found to result in dose-dependent inhibition of cell viability and induction of apoptosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…In the current study, apoptosis was induced in the C2C12 myoblasts only at the 24 h period following exposure to geigerin (Figure 3). Previous studies have reported induction of apoptosis by sesquiterpene lactones in cultured cells (Dirsch, Stuppner & Vollmar 2001; Zhang, Ong & Shen 2004; Zhang et al 2005, 2013). The presence of apoptotic cells was furthermore confirmed by TEM after exposure to geigerin (Figure 5).…”
Section: Discussionmentioning
confidence: 95%
“…In the current study, apoptosis was induced in the C2C12 myoblasts only at the 24 h period following exposure to geigerin (Figure 3). Previous studies have reported induction of apoptosis by sesquiterpene lactones in cultured cells (Dirsch, Stuppner & Vollmar 2001; Zhang, Ong & Shen 2004; Zhang et al 2005, 2013). The presence of apoptotic cells was furthermore confirmed by TEM after exposure to geigerin (Figure 5).…”
Section: Discussionmentioning
confidence: 95%
“…Khan et al (15) demonstrated that alantolactone induced cell apoptosis via GSH depletion and ROS generation in glioblastoma cells. Zhang et al (24) reported that alantolactone induced cell apoptosis via ROS generation in RKO cells.…”
Section: Discussionmentioning
confidence: 99%
“…These are the death receptor pathway and the mitochondria pathway [1-3]. Caspases, a family of cysteine proteases, play a critical role in apoptosis [4]. In addition, mitochondrial-dependent apoptosis is regulated principally by the Bcl-2 family proteins, such as Bax, Bcl-2 and Bak [5].…”
Section: Introductionmentioning
confidence: 99%